Pengaruh Model Pembelajaran Cooperative Script Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP N 1 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Agustina Manik; Oktober Tua Aritonang; Sudirman lase; Tianggur Medi Napitupulu; Goklas J. Manalu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to find out more about the influence of the Cooperative Script Learning Model on the Learning Activeness of Christian Religious Education for Class VIII Students of SMP N 1 Tarutung, North Tapanuli Regency for the 2023/2024 Academic Year. The research method used is a quantitative method with a pre-experimental design research type in the form of